A Educação Profissional, Científica e Tecnológica e os APLS: Instituto Federal de Sergipe e o APL de Tobias Barreto - Jesus, Pedro Augusto Silva de (2021)
Law 11,892 of December 29, 2008, which creates federal institutes, in article 6, brings as one of its purposes and characteristics: I- to offer professional and technological education, at all its levels and modalities, with emphasis on local, regional, and national socioeconomic development; IV - to guide its formative offer for the benefit of the consolidation and strengthening of local productive, social, and cultural arrangements. In Article 7, Law 11,892 establishes as one of the objectives of the Federal Institutes - IFs: III - to carry out applied research, stimulating the development of technical and technological solutions, extending its benefits to the community; IV - develop extension activities according to the principles and purposes of professional and technological education, in conjunction with the world of work and social segments, and with emphasis on the production, development and dissemination of scientific and technological knowledge. In this sense, this research aims to analyze the contribution of the IFS in generating innovation for the development of the APL in the city of Tobias Barreto. Considering the objectives of the study, the applied modality of the research was exploratory and descriptive, based on qualitative approach. For this, a bibliographic survey was carried out on Local Development, Local Productive Arrangement, Innovation and Triple Helix Theory, presenting its main concepts, theories, and authors; documentary research was also carried out on laws and documents relating to the Federal Institutes; data were collected from teaching, research, extension, intellectual property and technology transfers of the Federal Institute of Sergipe and The Tobias Barreto Campus. For data collection, a questionnaire was used, which was applied to the 12 teachers crowded at the Tobias Barreto Campus, as well as a semi-structured interview was used with each of the representatives of the Triple Helix: a representative of the FIS, two government representatives and Three representatives of the Productive Sector of the city. Based on the data collected throughout the research, we observed that the contribution of FIS in the generation of innovation, promoting the production, development and transfer of technologies, focusing on the problems Tobias Barreto's APL, is still very incipient, however, we have come to the conclusion that the IFS today has an important role in generating innovation, the structure the Tobias Campus Barreto, can provide the approach with Companies, with the Government in an approach similar to that of the Triple Helix.